Frequency, clinical presentation, and management of Bartholin’s abscess: A case study at Rabia Balkhi Hospital, Afghanistan in 2022 - Hamidi, Hamida (Svāsthya: Trends in General Medicine and Public Health, 2025)
Bartholin gland abscesses represent a significant gynecological condition requiring proper clinical management to prevent complications. These abscesses develop from ductal obstruction or infection of the bartholin glands, manifesting as localized pain, swelling, and erythema. Understanding their clinical presentation and management is crucial for optimal patient care in resource-limited settings. This study aimed to evaluate the incidence, clinical presentation, management strategies, and treatment outcomes of bartholin gland abscesses at Rabia Balkhi Hospital, Afghanistan, in 2022. This retrospective cohort study analyzed the hospital records of women diagnosed with Bartholin's gland abscesses. The study identified 23 cases (n = 23), representing 0.6% of all gynecological admissions. The data collected included demographic information, clinical presentations, treatment approaches, and outcome measures. Among the 4,140 gynecological admissions, 23 cases (0.6%) of Bartholin gland abscesses were identified. The majority of cases (52%) occurred in women aged 25-35 years, with predominant clinical manifestations, including severe localized pain (96%), erythema (96%), and swelling (87%). This study employed three primary treatment modalities: incision and drainage (74%), marsupialization (17%), and drainage tube insertion (9%). Treatment outcomes demonstrated favorable results, with pain resolution achieved in 87% of patients within 48 hours postintervention. The overall recurrence rate was 13%, with no major complications observed during the study period. Bartholin gland abscesses predominantly affect women aged 25-35 years, and incisions and drainage are the most effective treatments. These findings emphasize the importance of early intervention and appropriate treatment selection on the basis of patient characteristics